Biological and Genomic Characterization of a Novel Jumbo Bacteriophage, vB_VhaM_pir03 with Broad Host Lytic Activity against Vibrio harveyi - Gerald N. Misol; Constantina Kokkari; Pantelis Katharios (Pathogens, 2020)
Vibrio harveyi is a Gram-negative marine bacterium that causes major disease outbreaks and economic losses in aquaculture. Phage therapy has been considered as a potential alternative to antibiotics however, candidate bacteriophages require comprehensive characterization for a safe and practical phage therapy. In this work, a lytic novel jumbo bacteriophage, vB_VhaM_pir03 belonging to the Myoviridae family was isolated and characterized against V. harveyi type strain DSM19623. It had broad host lytic activity against 31 antibiotic-resistant strains of V. harveyi, V. alginolyticus, V. campbellii and V. owensii. Adsorption time of vB_VhaM_pir03 was determined at 6 min while the latent-phase was at 40 min and burst-size at 75 pfu/mL. vB_VhaM_pir03 was able to lyse several host strains at multiplicity-of-infections (MOI) 0.1 to 10. The genome of vB_VhaM_pir03 consists of 286,284 base pairs with 334 predicted open reading frames (ORFs). No virulence, antibiotic resistance, integrase encoding genes and transducing potential were detected. Phylogenetic and phylogenomic analysis showed that vB_VhaM_pir03 is a novel bacteriophage displaying the highest similarity to another jumbo phage, vB_BONAISHI infecting Vibrio coralliilyticus. Experimental phage therapy trial using brine shrimp, Artemia salina infected with V. harveyi demonstrated that vB_VhaM_pir03 was able to significantly reduce mortality 24 h post infection when administered at MOI 0.1 which suggests that it can be an excellent candidate for phage therapy.